GAMBARAN KEJADIAN OBESITAS, ASUPAN GIZI DAN AKTIVITAS FISIK BERDASARKAN STATUS ANDROPAUSE PADA PRIA USIA 30-50 TAHUN (Studi di Kecamatan Tembalang Kota Semarang) - Rofida Ulinnuha; Ari Udiyono; Mateus Sakundarno Adi; M. Arie Wuryanto (Jurnal Kesehatan Masyarakat (Undip), 2018)
Andropause is a syndrome caused by reduction of testosterone level followed by decline of physical, psychological and sexual abilities in older men. Reduction of testosterone is accelerate by external factors such as the increase of body fat or commonly called obesity. In addition, nutritional intake and physical activity affect to body fat, it also known affect testosterone level through hormone circulation. The purpose of this study is to describe obesity incidence, nutritional intake and physical activity based on andropause status among men 30-50 years old in Tembalang District. The type of this research is descriptive study with cross sectional design. The sample size in this study are 100 men among 30-50 years old selected by criterias of study. Sample size divide by population among men 30-50 years old in each sub-district using proportional stratified random sampling, then it selected using purposive sampling. The resultshowed that based on andropause status, respondent who had andropause are 56%, 60% of them had BMI classified as obesity, 61,7% had body fat percentage classified as obesity, 66.7% had waist circumference classified as central obesity, 57,4% had less energy intake, 71.4% had excessive protein intake, 59.4% had normal fat intake, 58% had less Zinc intake and 67.8% had low physical activity. It is recommended to control weight and physical activity regularly.